Condutas terapêuticas para caninos inclusos - Gaetti-Jardim, Ellen Cristina [UNESP] (2012)
Normally, the last teeth to erupt are the ones which remain impacted or semi-impacted, and that is the case of the canines. This study aimed to report a few options of treatment, aiming at esthetic and functional maintenance of the affected area before a impacted canine, discussing its indications, contraindications, advantages and disadvantages. This study also aims to emphasize the accessibility the patient would have in case his/her option were one of the approached ways of treatment. In order to identify the studies included or analyzed in this review, a detailed search strategy was performed for the database used: Pubmed, Bireme, Scielo, Cochrane, and Dentistry Oral Science up to 2011. We used non-erupted teeth, canine, and therapeutics as descriptors. The criteria of inclusion were clinical and review articles that approached the theme. Through this review, it was found that the surgeon dentist’s lack of technical and scientific knowledge and the financial impossibility of most population are some hindrances for the establishment of the right planning for the impacted canine.